Sleepy Hollow sleepover - Roy, Ron, 1940-; Gurney, John Steven, 1962-; Irving, Washington, 1783-1859. (New York : Random House, 2010)
Dink, Josh, and Ruth Rose are enjoying Halloween fun in Sleepy Hollow, New York, but when unplanned spooky things start happening, they investigate whether a real headless horseman might be to blame.
"A Stepping Stone book."
3.8
3-6
Keywords: Halloween -- Juvenile fiction; Brigands and robbers -- Juvenile fiction; Sleepy Hollow (N.Y.) -- Juvenile fiction; Mystery and detective stories; Halloween -- Fiction; Robbers and outlaws -- Fiction; Sleepy Hollow (N.Y.) -- Fiction; Mystery fiction; Halloween -- Fiction; Thieves -- Fiction; Sleepy Hollow (N.Y.) -- Fiction